Economic Growth Analysis in Surabaya City: An LQ, Dynamic LQ, Klassen Typology and Shift-Share Approach - Ananda Rafly Dheny Syahputra; Marseto Marseto; Anisa Fitria Utami (Journal of Macroeconomics and Social Development, 2026)
This study aims to identify economic sectors that serve as base, potential, competitive, and leading sectors in Surabaya City, East Java. As a primary trade gateway for Eastern Indonesia and a regional economic hub, Surabaya's development is reflected in its Gross Regional Domestic Product (GRDP) data. This research employs a descriptive quantitative method using secondary data from the Central Bureau of Statistics (BPS). The analysis utilizes Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift-Share, and Overlay analysis to draw conclusions. The results identify four leading sectors in Surabaya: Manufacturing Industry; Electricity and Gas Supply; Wholesale and Retail Trade (including Car and Motorcycle Repair); and Accommodation and Food Services. These findings provide strategic insights for policymakers to formulate economic development strategies aimed at enhancing regional economic growth.